2011
DOI: 10.1097/mph.0b013e31822031d9
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Central Nervous System Tumors

Abstract: The objective of this study was to determine the epidemiology of primary tumors of the central nervous system (CNS) in pediatric patients from a Brazilian oncology institute. We retrospectively analyzed 741 charts (415 males and 326 females) of patients under 21 years of age who were diagnosed with a CNS tumor. The analysis included patients from 1989 to 2009 and was performed using the World Health Organization criteria. We evaluated the distribution of age, sex, topography, clinical symptoms, symptom interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Other studies around the world have reported similar ratios: 1.1 in France (population-based study), 1.31 in Japan (population-based study), and 1.27 in Brazil (single-center study) [9,10,12]. From our data, males accounted for 74.4% of the germ cell tumors in the pediatric cases, a percentage that was similar to the 69.6% reported by CBTRUS and to those reported by other studies from various regions [8-12], indicating that intrinsic factors also play important roles in oncogenesis.…”
Section: Discussionmentioning
confidence: 52%
“…Other studies around the world have reported similar ratios: 1.1 in France (population-based study), 1.31 in Japan (population-based study), and 1.27 in Brazil (single-center study) [9,10,12]. From our data, males accounted for 74.4% of the germ cell tumors in the pediatric cases, a percentage that was similar to the 69.6% reported by CBTRUS and to those reported by other studies from various regions [8-12], indicating that intrinsic factors also play important roles in oncogenesis.…”
Section: Discussionmentioning
confidence: 52%
“…In other studies from Brazil, Nigeria, Pakistan, Medulloblastomas were the second most common. [ 18 20 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by four major subgroups, one of which displays constitutively activated Sonic Hedgehog (SHH) signaling. 1417 BMP2 and BMP4 antagonize SHH signaling, 18 and BMP4 signaling induces irreversible differentiation of cerebellar granule neuronal progenitors (GNPs) and tumor cells from the SHH medulloblastoma subgroup. 19 This finding suggested that BMP agonists might be useful as differentiation therapy for SHH medulloblastoma.…”
Section: Introductionmentioning
confidence: 99%